TRANSFORMASI PENDIDIKAN EKONOMI: MENGEKSPLORASI MANFAAT, TANTANGAN, DAN IMPLEMENTASI LABORATORIUM VIRTUAL - Ahmad, Iswadi M; Habsyi, Faisal Y (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
The development of information and communication technology has changed the educational paradigm, including economic education in universities. One of the innovations that has emerged is the virtual laboratory, which allows students and lecturers to carry out practices and experiments without the need for a physical laboratory. This article explores the benefits, challenges, and implementation of virtual laboratories in the context of economics education. This research uses a qualitative method with a literature review approach and applies the PRISMA (Preferred Reporting Items For Systematic Reviews and Meta Analysis) method for data collection. Data analysis was carried out through critical appraisal of selected literature. Virtual laboratories allow students to engage in market simulations, economic policy experiments, data analysis, and economic modeling. This not only deepens theoretical understanding, but also develops practical skills such as data analysis and decision making. Lecturers can use virtual laboratories to increase teaching effectiveness and provide faster feedback to students. However, the implementation of virtual laboratories faces a number of challenges such as adequate technological infrastructure, development of relevant content, integration with existing teaching methods, effective assessment, and professional training for educators. Overall, virtual laboratories have great potential to improve the quality of economics education by providing a more interactive and in-depth learning experience for students, and preparing them to face future economic challenges.